Um estudo sobre as dimensões que contribuem para a adoção da construção civil sustentável. - Marques, Mauricio Dias [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
This study proposes to evaluate, together with potential construction consumers, the relationship between factors or dimensions, such as environmental awareness, knowledge about sustainable civil construction and the barriers to its adoption, which are reflected in the consumer's decision to adopt sustainable civil construction. To do so, the study seeks to identify materials that can be used as raw materials for civil construction with less disastrous results for the environment; to understand Brazilian and foreign legislation on the management of solid waste from civil construction; to understand concepts and opinions that report possibilities, problems and difficulties of sustainability in civil construction; and, finally, to evaluate the relationship between the dimensions that can lead the consumer to adopt sustainable civil construction. This is a descriptive, qualitative and quantitative study, starting with bibliographic and documentary research and concluding with field research in the form of a questionnaire to enable comparison through a statistical model of structural equations. From this reflection, it was noted that the lack of frequency in the adoption of sustainable civil construction is linked to the lack of public policies to stimulate and the lack of integration of incentives for all sectors involved.

Este estudo propõe avaliar, junto a potenciais consumidores da construção civil, a relação entre fatores ou dimensões, como a consciência ambiental, o conhecimento sobre construção civil sustentável e as barreiras para sua adoção, que refletem na decisão da adoção da construção civil sustentável pelo consumidor. Para tanto, busca-se conhecer materiais que podem compor a matéria prima da construção civil com resultados menos desastrosos ao ambiente; conhecer a legislação brasileira e estrangeira sobre o gerenciamento dos resíduos sólidos da construção civil; conhecer conceitos, pareceres e opiniões que relatam possibilidades, problemas e dificuldades da sustentabilidade na construção civil e, por fim, avaliar a relação das dimensões que podem levar o consumidor a adotar a construção civil sustentável. Trata-se de pesquisa descritiva, qualitativa e quantitativa, partindo-se de pesquisa bibliográfica e documental e concluindo com pesquisa de campo na modalidade de questionário para possibilitar a comparação por meio de modelo estatístico de equações estruturais. Percebeu-se, dessa reflexão, que a falta de frequência na adoção da construção civil sustentável está vinculada à falta de políticas públicas de estímulo e falta de integração de incentivo de todos os setores envolvidos.
A study on the dimensions that contribute to the adoption of sustainable civil construction.
Keywords: Construção civil; Sustentabilidade; Arquitetura sustentável; Engenharia sustentável; Consumidor